Performance of Wind Exposed Structures Results of the PERBACCO project - Ricciardelli, Francesco; Sepe, Vincenzo; Bartoli, Gianni; Saetta, Anna (Proceedings e report, 2006)
PERBACCO (a free Italian acronym for Life-cycle Performance, Innovation and Design Criteria for Structures and Infrastructures Facing Æolian and Other Natural Hazards) is a research project partly funded by the Italian Ministry for University (MIUR) in the PRIN (Progetti di Ricerca di Interesse Nazionale) framework, for the years 2004-05.Within the project, a first attempt has been made to integrate different disciplines aiming at an overall optimization of the performance of a wide range of wind exposed structures and infrastructures, with consequent benefi cial impact on the society.The overall objectives were (a) to provide unifi ed concepts for "expected performance" and "risks induced by æolian and other natural hazards", to be applied to structures and infrastructures over their whole life-cycle, such to be acceptable to stakeholders in the construction process (i.e. from the owner to the end-user), (b) to provide models and methodologies for dynamic monitoring of the performance of structures and infrastructures, to be integrated in appropriately designed procedures, and (c) to collect, refi ne, fi le and disseminate the knowledge available on a European basis, concerning the performance of wind-exposed structures and facilities, in a way such to be of use to Construction Industry. This volume summarises the main results obtained during the Project, with each Section addressing a different class of problems, to which many research Units have contributed. A list of papers containing the main results of the research activities carried out within the Project is also provided in each Section.